180k views
5 votes
_9) What are the solutions of the equation (x – 3)2 + 2(x – 3) - 8 = 0?

A) x = -5 and x = 1
B) x = -1 and x = 5
C) x = -1 and x = -7
D) x = 1 and x = 7
Help please

1 Answer

4 votes

Answer:

Explanation:

Two numbers r and s sum up to \frac{1}{2} exactly when the average of the two numbers is \frac{1}{2}*\frac{1}{2} = \frac{1}{4}. You can also see that the midpoint of r and s corresponds to the axis of symmetry of the parabola represented by the quadratic equation y=x^2+Bx+C.

User Asi
by
5.9k points